An enigmatic new genus of cyclostome braconid wasp (Hymenoptera: Braconidae) from New Zealand - Belokobylskij, Sergey A. (Zootaxa, 2018)
A new enigmatic genus perhaps belonging to the braconid wasp subfamily Pambolinae, Zeachremylus gen. nov. (type species Z. wardi sp. nov.), is described from New Zealand. The taxonomic position of this new genus is discussed.